Gerakan Petani Banten: Studi Tentang Konfigurasi Sufisme Awal Abad Xix - Hamidah Hamidah (Ulumuna, 2010)
Sufism is an esoteric dimension of Islam, which differs from the outer aspect of Islam known as shari’a. This view did not emerge at the early time because Sufism was not regarded as the inner manifestation of Islam, as it is so now. Rather, it was seen as Islam itself. Tarekat in its initial phase constituted associations of people who wanted to escape from a worldly life. However, this orientation shifted since the associations broadened their roles into socio-political life by engaging in revolts against colonialism as it occurred in Banten in 1888. This peasant revolt movement was not an independent move without a significant contribution from the sufi brotherhood since actors in the revolt were members of tarekat. According to Banten Residen, almost all of the employees in his office including police were the members of tarekat. One salient feature of the movement is concerned with the xenophobic spirit that rejected the presence of foreigners and advocated a holy war.